Thirty Years Later: Evolution of Treatment for Acute Left Main Coronary Artery Occlusion - Moshe Y. Flugelman; Nissan Ben-Dov; Basheer Karkabi; Ronen Jaffe (Case Reports in Cardiology)
Acute occlusion of left main coronary artery is a catastrophic event. We describe two patients with acute occlusion of the left main coronary artery treated thirty years apart. The first patient was treated in 1982 and survived the event without revascularization but developed severe heart failure. His survival was so unusual that it merited a case report at that time. The second patient was treated at the end of 2015. Early revascularization resulted in myocardial reperfusion and near normal left ventricular function. These patients exemplify the progress in therapeutic cardiology over the last 30 years.